A Novel Three-phase integrated inverter for Hybrid Electric Vehicle Applications - Tatarao Donepudi; Anupalli Immanuel (Journal of Technology Informatics and Engineering, 2026)
Multilevel inverters (MLIs) have become essential in power electronics due to their capability to improve power quality, minimize harmonic distortion and enhance efficiency in medium and HV applications. It achieves smoother waveform, reducing total harmonic distortion (THD). Hybrid electric vehicles (HEVs) are increasingly recognized for their ability to reduce fuel consumption and emissions in modern transportation. Their performance largely depends on the efficiency of power conversion systems, particularly in inverter setup. In this study a novel 3-phase 25-level MLI configuration is proposed with a fewer switches. The primary objective is to reduce harmonics through high-level MLI implementation and motor optimization in electric vehicle applications.  Proposed research suggests a novel three-phase 25-level hybrid inverter tailored for hybrid electric vehicles, featuring innovative hybrid DC-DC and DC-AC topologies that utilize fewer switches to enhance cost-effectiveness. Simulation results indicate, the three-phase 25-level MLI improves voltage stability and further mitigates harmonics compared to single-phase configuration. While comparing with conventional converters, MLIs offer significant benefits, including high-frequency switching and advanced modulation techniques for precise control. It generates output voltage with minimal harmonics, lower dv/dt stress on switches and introduces common-mode voltage. In particular, the 3-phase 25-level inverter system, achieves a smoother waveform, reducing total harmonic distortion (THD). The proposed system has been validated using MATLAB/Simulink. Additionally, the comparative analysis between proposed 1-ph. and 3-ph. 25-level MLI topologies also presented.